SISTEM INFORMASI PERPUSTAKAAN MENGGUNAKAN QR CODE PADA SMP NEGERI 6 KEMPAS BERBASIS WEB - Aditia, Febri; Yunita, Fitri; Ilyas, Ilyas; Rozi, M. Sahrul (Universitas Lampung, 2024)
Information technology has developed very rapidly nowadays, this has had a significant influence on human activities, such as making various fields of human work easier. One of these technological developments is the Library Information System. The Library of SMP Negeri 6 Kempas currently still uses media in the form of master books as storage media to manage library data. Storage that uses master books has the potential to experience many problems such as data loss because master books are easily torn, faded or lost, inaccuracies in reports, the length of the book management process and many other problems. The aim of this research is to produce a website-based library information system using QR Codes that can be used to handle the service process and book data management at the SMP Negeri 6 Kempas library and overcome the problems and weaknesses that occur when using the old system that is currently in use. The result of this research is to produce a Web-based QR Code Library Information System and has passed system Functionality testing with a score of 100% and Usability with a score of 81.6%.